1991
DOI: 10.1002/j.1552-4604.1991.tb03673.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and Pharmacokinetics of Amiodarone

Abstract: Amiodarone is a unique antiarrhythmic agent originally developed as a vasodilator. Classified electrophysiologically as a Type III antiarrhythmic, it also has both nonspecific antisympathetic and direct, fast channel-membrane effects. Hemodynamic effects of orally administered amiodarone (a negative inotropic agent) are usually negligible, and are usually compensated for by induced vasodilation. Effects on thyroid and hepatic function may help to explain some of the unique pharmacologic as well as toxicologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…It was reported that amiodarone could undergo extensive enterohepatic circulation (Freedman and Somberg, 1991;Roden, 1993). Glucuronidation of the metabolites and biliary excretion was thought to be the final elimination process for amiodarone (Freedman and Somberg, 1991). However, the phase II metabolism of amiodarone had not been comprehensively studied, although there is indirect evidence (after hydrolysis) for glucuronide metabolites of amiodarone in human plasma (Ha et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that amiodarone could undergo extensive enterohepatic circulation (Freedman and Somberg, 1991;Roden, 1993). Glucuronidation of the metabolites and biliary excretion was thought to be the final elimination process for amiodarone (Freedman and Somberg, 1991). However, the phase II metabolism of amiodarone had not been comprehensively studied, although there is indirect evidence (after hydrolysis) for glucuronide metabolites of amiodarone in human plasma (Ha et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the deiodination of amiodarone is still unclear and is a topic of considerable debate. A previous study proposed that deiodination was one of the metabolic pathways of amiodarone in humans (Freedman andSomberg, 1991), andYoung andMehendale (1986) reported that MDEA could be dideiodinated in rabbit liver microsomes. However, others claimed that no deiodinated metabolites could be found in vivo and in vitro (Ha et al, 2001a(Ha et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This might be due to enterohepatic recirculation of CRA13 because drugs subject to enterohepatic recirculation are often characterized by multiple peaks and a long half-life (e.g., estradiol) (Vree and Timmer, 1998). Likewise, compounds of many other classes such as sulfonamide diuretics (Vree and van der Ven, 1999), antiarrhythmic drugs (Freedman and Somberg, 1991), or nonsteroidal anti-inflammatory drugs (Busch et al, 1995) are also subjected to enterohepatic recirculation. In addition, the bile salts, released after meal ingestion, could have facilitated further dissolution and solubilization of CRA13 [solubility in water, ϳ0.001-0.002 mg/ml; log partition coefficient (log P) ϭ 6.9], allowing a second absorption phase.…”
Section: Discussionmentioning
confidence: 99%